Association Between Oyster Consumption and Hemoglobin Concentrations Among Ghanaian Women. (14th June 2022) - Abreu, Alyssa; Bentil, Helena; Okronipa, Harriet; Fiorella, Kathryn; Vadiveloo, Maya; Gomez-Chiarri, Marta; Whewell, Austin; Adu-Afarwuah, Seth; Oaks, Brietta
Abstract: Objectives: Oysters are a rich source of iron and consumption may reduce the risk of anemia. In 2017, a community in Ghana implemented an annual closed season of oyster harvesting between November–March, designed to benefit the sustainability of oyster harvesting. Our objectives were to determine the effect of the open and closed season on oyster consumption and anemia. Methods: In a 6-month, longitudinal pilot study, we enrolled women in the Bortianor/Tsokomey area in Ghana and included 96 who regularly consume oysters during the open season and 40 who do not. Data were collected at two time points: 1) March 2020 (end of closed season) and 2) August 2020 (5 months into the open season). We collected the amount and frequency of oyster consumption using a 30-day food frequency questionnaire. We analyzed hemoglobin (Hb) concentrations using a Hemocue Analyzer 201. We used paired t-tests to analyze the difference in Hb concentrations and McNemar's test for anemia (Hb < 12.0 g/dL) between seasons and used independent t-tests between groups. Results: At enrollment, mean ± SD age was 34 ± 8 y and BMI was 26 ± 5 kg/m 2 . Among women who ate oysters during the open season, Hb did not differ by season (closed season mean ± SD: 10.4 ± 2.6, open season: 9.8 ± 2.8, p = 0.06) and the prevalence of anemia was 74% in the closed season and 72% in the open season (p = 0.81). For women who did not eat oysters during the open season, Hb did not differ by season (closed season Hb mean ± SD: 9.6 ± 2.2, open season Hb: 9.9 ± 2.3, p = 0.15) and the prevalence of anemia in the closed season was 84%, and 78% in the open season (p = 0.35). During the open season, mean ± SD oyster consumption among women who ate oysters was 1726 ± 1685 grams, or 470 oysters per month. There was no difference between groups in Hb and anemia prevalence during the closed (Hb: p = 0.17, anemia: p = 0.16) or open (Hb: p = 0.15, anemia: p = 0.49) season. Conclusions: The prevalence of anemia was high during both seasons in both groups of women. Implementing a closed season on oyster harvesting was not related to a higher prevalence of anemia among women that eat oysters. Further research into the causes of anemia among this population is needed and programmatic action to address the high prevalence of anemia in women of reproductive age is warranted in this area. Funding Sources: University of Rhode Island start-up grant, awarded to Dr. Brietta M. Oaks.